Welfare resilience in the immediate aftermath of the COVID-19 outbreak in Italy - Francesco Figari; Carlo V. Fiorio (University of Essex, Institute for Social and Economic Research (ISER), 2020)
This paper analyses the extent to which the Italian welfare system provides monetary compensation for those who lost their earnings due to the lockdown imposed by the government in order to contain the COVID-19 pandemic in March 2020. In assessing first-order effects of the businesses temporarily shut down and the government's policy measures on household income, counterfactual scenarios are simulated with EUROMOD, the EU-wide microsimulation model, integrated with information on the workers who the lockdown is more likely to affect. This paper provides timely evidence on the differing degrees of relative and absolute resilience of the household incomes of the individuals affected by the lockdown. These arise from the variations in the protection offered by the tax-benefit system, coupled with personal and household circumstances of the individuals at risk of income loss.
Keywords: C81; D31; H55; I30; 330; pandemic; household income; microsimulation; Italy